Comparative analysis of cost, emissions and fuel consumption of diesel, natural gas, electric and hydrogen urban buses. (1st April 2022) - Muñoz, Pedro; Franceschini, Esteban A.; Levitan, David; Rodriguez, C. Ramiro; Humana, Teresita; Correa Perelmuter, Gabriel
Highlights: The study is framed in Argentina for 4 urban bus fleets with different powertrains. For the integrated index the Battery Electric Bus becomes the best option by 2023. Fuel Cell Bus turns out to be the best option from 2027 onwards. Hydrogen cost is the most sensitive parameter in the total cost of fuel cell buses. Transition of the entire urban buses fleet is beneficial in all the analyzed indexes. Abstract: Within the context of the energy transition, there are several alternatives under study for the gradual replacement of diesel fuel based urban transport vehicles. This paper proposes an answer to the following question: Which bus technology and energy mix is more efficient in terms of cost, energy consumption and greenhouse gas emissions? A method is proposed to compare different urban bus fleet technologies, using an integrated index composed of three indices that measure well-to-wheel energy use, global warming potential in terms of carbon dioxide equivalent emissions, and total cost of ownership. The method is applied to the case of Argentina, from the 2019 scenario to the year 2030, and the results for each index show that, (i) even for the current energy scenario, battery and hydrogen fuel cell buses show a decrease in greenhouse gas emissions; that (ii) today the compressed natural gas bus is a better mean of passenger transport for both urban and intercity uses (it could reduce the carbon dioxide equivalent emissions 10.07% and the total cost of ownership 5.3%); and that (iii) both battery and hydrogen fuel cell vehicles become cost competitive with compressed natural gas and diesel vehicles over the course of the current decade. In addition, (iv) the battery electric bus is shown to become the best option by 2023 and (v) the hydrogen fuel cell bus proves to be the best option from 2027 onwards. The transition of the entire urban bus fleet in Argentina to zero-emission technologies is expected to be beneficial from the point of view of energy consumption, environmental emissions and the economy. If transition of the whole fleet to Hydrogen fuel cell buses is carried out, 1.3 Mt of carbon dioxide equivalent emissions could be reduced, which represents a 87% reduction in green house gases emissions, and if the transition is to battery electric buses, the energy consumption would be reduced by between 25 and 38% and emissions by between 52 and 61% abating around 0.93 Mt of carbon dioxide equivalent per year.